PENGARUH DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO PAKAIAN MUSLIM ILHAM - Nabila Dwi Cahyani; Elizabeth Tika Kristina Hartuti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstract. This study aims to determine the effect of Digital Marketing and service quality on customer satisfaction at Ilham Muslim Clothing Store in Cisauk, Tangerang Regency. The research method used is an associative method with a quantitative approach. Data collection was carried out by distributing questionnaires to 97 respondents selected using the Slovin technique from a population of 3,656 consumers. The data were analyzed using validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination to examine the effect of the independent variables, namely Digital Marketing (X1) and service quality (X2), on the dependent variable of customer satisfaction (Y). The results showed that Digital Marketing had a positive and significant effect on customer satisfaction with a t-value of 9.475 > 1.661 and a significance of 0.000. Service quality also had a positive and significant effect on customer satisfaction with a t-value of 10.890 > 1.661 and a significance of 0.000. Simultaneously, Digital Marketing and service quality have a positive and significant effect on customer satisfaction with an F-value of 73.294 > 3.093 and a determination value of 60.9%. Thus, the better the implementation of Digital Marketing and service quality, the higher the level of customer satisfaction at Ilham Muslim Clothing Store. Keywords: Digital Marketing, Service Quality, Customer Satisfaction